Supply chain visibility and security – the SMART-CM project solution. (1st January 2014) - Boile, Maria; Sdoukopoulos, Lefteris
In a business environment characterised by increasingly complex supply chains forming a highly competitive marketplace, information sharing and visibility have become prerequisites for achieving efficient and effective supply chain management, facilitating decision making and enhancing cooperation among supply chain industry partners. To this end, technology plays a vital role, offering great opportunities for businesses ranging from tactical and operational to the creation of a strategic advantage. Technological solutions for improving supply chain visibility and security have been identified as a top priority and issues of utmost importance to industry parties and public authorities alike. This paper highlights the needs and benefits derived from improved visibility and collateral benefits to supply chain security and presents a relevant technological solution developed within the SMART-CM research project. The paper focuses on the benefits that can be realised by the various supply chain stakeholder groups from the adoption of this technology, addressing their needs.